ARSITEKTUR PERCABANGAN POHON DI RUANG TERBUKA HIJAU KOTA PEKANBARU SEBAGAI BAHAN AJAR BOOKLET MATERI KLSIFIKASI TUMBUHAN DI SMA - Veren Vivin; Wan Syafi’i; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Tree branching architectural model material as teaching material Booklet of plant classification material for high school level. Research has been carried out to record the diversity of architectural models of tree branching in the Green Open Space (Green Open Space) of Pekanbaru City Forest in January 2022. This research uses a survey method to directly identify all tree species found in Pekanbaru City Forest Green Open Space, documentation, and identification indirectly by referring to the book by F. Halle & R.A.A. Oldeman, with the title: An Essay On The Architecture and Dynamics of Growth of Tropical Trees. The objects in this study are the main branching of the main branch, the nature of its growth, the direction of branch growth, and the place where the flowers appear. This research booklet is designed for plant classification material. The design of the booklet was carried out in February 2022. There are two stages of making booklet teaching materials, namely the analysis stage and the design stage. The analysis phase consists of curriculum analysis and subject matter analysis. The design stage includes making lesson plans and designing booklets. The results showed that there were 11 types of tree branching architectural models or 47.82% of the 23 existing tree architectural models. The 11 types of architectural models consist of 34 species of trees in the open space of the Pekanbaru City Forest, namely Aubreville, Corner, Koriba, Leeuwenberg, Massaart. McClure, Prevost, Rauh, Roux, Scarrone, and Troll. In addition, booklet teaching materials are produced that can be used as additional references for Biology learning, especially Plant Classification materials.Key Words: Tree branching architectural model, Green Open Space, Bookle.